Dispersal-based processes as drivers of fish communities and species distributions in the Yangtze River–Poyang Lake riverine floodplain of China - Chang, Tao; Li, Mingzheng; Gao, Xin (Ecological processes, 2025)
Background The assembly processes of fish communities in large complex ecosystems often exhibit spatiotemporal variation. In riverine floodplains, this variation is also influenced by interactions with the river main-stem during the flood pulse, which often masks and confounds the driving factor of community structure. Herein, we investigated the distribution patterns of fish communities along the landscape gradient in the Yangtze River–Poyang Lake riverine floodplain (YPF) of China, with the goal of understanding assembly processes that shape fish communities among different habitats and their possible linkage to hydrological disturbances. Results Fish communities in the Yangtze River (YR), Yangtze River-channel ecotone (CYR), Poyang Lake-channel ecotone (CPL), and Poyang Lake (PL) exhibited significant spatial differentiation. Across different hydrological periods, channel ecotones act as buffer zones that can potentially provide stable habitats. For example, communities within channel ecotones (i.e., CYR and CPL) typically exhibited lower temporal variability than permanent lotic (YR) or lentic (PL) waters. Applying the newly proposed dispersal-niche continuum index (DNCI) framework, we quantified a profound dispersal effect among the fish communities across four habitats, especially during flood seasons when the river and lake channels were highly connected. Notably, the niche-related process was not prominent during low-flow conditions, which might be explained by the incomplete isolation of the PL and YR by the water channel. Conclusions The application of DNCI effectively quantified the driving mechanisms of YPF fish communities among different habitats across different hydrological conditions while visually representing lateral dispersal as the main driver of community distribution patterns. This study emphasizes the importance of the lateral hydrological connectivity of the riverine floodplain, which should be considered during conservation efforts aimed at restoring the natural river–lake network necessary for fish diversity to flourish.